BIBLICAL AND PHILOSOPHICAL REFLEXION OF C. S. LEWIS TREATISE ‘SUFFERING’ - Lyudmila N. Efimova; Natal'ya A. Shekhireva (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article deals with creative work of Clive Staples Lewis and in particular his philosophical treatise ‘Suffering’. This work shows in the most comprehensive way philosophical and spiritual quests of C.S. Lewis as a Christian advocate and religious thinker. The authors highlight issues of God’s grace, paradise and hell, of faith, human imperfection, suffering of man and animals that were discussed in the treatise. They came to the conclusion that deep understanding of suffering by Lewis allows us to characterize him as one of the wisest advocates of the 20th century startling with his extraordinary erudition. In ‘Suffering’ and other essays and articles Lewis proved himself as an excellent expert of the Holy Writ and works by Saint Fathers of the church.